2014
DOI: 10.5888/pcd11.140361
|View full text |Cite
|
Sign up to set email alerts
|

Improving Children’s Menus in Community Restaurants: Best Food for Families, Infants, and Toddlers (Best Food FITS) Intervention, South Central Texas, 2010–2014

Abstract: BackgroundApproximately 32% of US children are overweight or obese. Restaurant and fast food meals contribute 18% of daily calories for children and adolescents aged 2 to 18 years. Changing children’s menus may improve their diets. This case study describes Best Food for Families, Infants, and Toddlers (Best Food FITS), a community-based intervention designed to address childhood obesity. The objective of this study was to improve San Marcos children’s access to healthy diets through partnerships with local re… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
22
0
1

Year Published

2016
2016
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 17 publications
(24 citation statements)
references
References 13 publications
(16 reference statements)
1
22
0
1
Order By: Relevance
“…Similar to a previous study [ 49 ], restaurants randomized to the menu-plus intervention condition are engaged in a more collaborative process of: (a) identifying healthy children’s menu items that may fit better with their existing adult and children’s menus (if available); (b) implementing a healthy children’s menu campaign that includes a printed children’s menu with copy and design elements that influence ordering behavior [ 50 ], a banner and table tents; and (c) kitchen staff and server training to prepare and promote the new healthy children’s menu items (see Table 1 ). Regarding the menu items, to maximize the sales of new children’s menu items, decisions about what items to include, their recipes, prices, etc., are made over three to four meetings with the restaurant manager/owner.…”
Section: Methodssupporting
confidence: 88%
See 1 more Smart Citation
“…Similar to a previous study [ 49 ], restaurants randomized to the menu-plus intervention condition are engaged in a more collaborative process of: (a) identifying healthy children’s menu items that may fit better with their existing adult and children’s menus (if available); (b) implementing a healthy children’s menu campaign that includes a printed children’s menu with copy and design elements that influence ordering behavior [ 50 ], a banner and table tents; and (c) kitchen staff and server training to prepare and promote the new healthy children’s menu items (see Table 1 ). Regarding the menu items, to maximize the sales of new children’s menu items, decisions about what items to include, their recipes, prices, etc., are made over three to four meetings with the restaurant manager/owner.…”
Section: Methodssupporting
confidence: 88%
“…Outside banners are used to draw dining parties with children into the restaurants. Table tents and banners are used to promote the menu items, similar to previous research [ 49 ]. The materials are designed to appeal to both children and adults given the increased autonomy children exhibit in restaurant ordering, compared with other food-related decisions [ 42 ].…”
Section: Methodsmentioning
confidence: 99%
“…According to the articles, low calorie dishes may be included in restaurants' menus through modifying cooking methods 4,20,22,24 , reducing portion size 4,17,19,20,[22][23][24] or adding appetizers with lower calories 4,18,23,24 . Likewise, sugar reduction in meals offered in these establishments was discussed 4,17,20,22,26,27 . On the other hand, reduction of sodium and saturated fat was mentioned repeatedly due to the high prevalence of cardiovascular disease in the population 4,20,24,[27][28][29] .…”
Section: Food Supply Modificationsmentioning
confidence: 99%
“…To illustrate this, Newson et al 4 asserted that healthy choices are often linked to the perception of less taste, less satiety and higher price. Given this trend, several establishments assume that providing this type of food will harm their profits 22,34 , even more so if foods with lower nutritional quality have a higher profit margin 25,26 . In fact, one study indicated a potential conflict between health promotion and profit generation in food outlets 35 .…”
Section: Barriers Against Healthy Eating Promotion In Restaurantsmentioning
confidence: 99%
“…However, a rural [ 64 ] and urban [ 65 ] study demonstrated that portions could be reduced if technical assistance and public recognition were offered to promote healthy restaurant programs. The fourth study was conducted in an urban city of Texas, and 12 of 17 restaurants reported using the healthy children’s menus two years after the intervention had ended [ 66 ].…”
Section: Resultsmentioning
confidence: 99%